Effects of intensive lipid lowering compared with moderate-intensity lipid lowering on coronary atherosclerotic plaque phenotype and major adverse cardiovascular events in adults with low to intermediate 10-year ASCVD risk (ILLUMINATION study): protocol for a multicentre, open-label, blinded-endpoint, randomised controlled trial - Yang Wang; Kefei Dou; Bin Lu; Jia Li; Jinqing Yuan; Zhihui Hou; Jianan Zheng; Xueyan Zhao; Wenjia Zhang (BMJ Open, 2023)
Introduction Current guidelines recommend moderate-intensity lipid lowering (low-density lipoprotein cholesterol, LDL-C of <2.6 mmol/L or 30%–49% reduction from the baseline) for patients with intermediate 10-year atherosclerotic cardiovascular disease (ASCVD) risk. The effects of intensive lipid lowering (LDL-C of <1.8 mmol/L) on coronary atherosclerotic plaque phenotype and major adverse cardiovascular events (MACE) in adults with both non-obstructive coronary artery disease (CAD) and low to intermediate 10-year ASCVD risk remain uncertain.Methods and analysis Intensive Lipid-lowering for Plaque and Major Adverse Cardiovascular Events in Low to Intermediate 10-year ASCVD Risk Population is a multicentre, randomised, open-label, blinded endpoint clinical trial. Inclusion criteria are as follows: (1) patients with the age of 40–75 years within 1 month of coronary CT angiography (CCTA) and coronary artery calcium score (CACS) evaluation; (2) population with low to intermediate 10-year ASCVD risk (<20%) and (3) patients with non-obstructive CAD (stenosis <50%) using CCTA. 2900 patients will be randomly assigned to the intensive lipid lowering (LDL-C of <1.8 mmol/L or ≥50% reduction from the baseline) or the moderate-intensity lipid lowering (LDL-C of<2.6 mmol/L or 30%–49% reduction from the baseline) group in a 1:1 ratio. The primary endpoint is MACE (composite of all-cause death, non-fatal MI, non-fatal stroke, any revascularisation and hospitalisation for angina) within 3 years after enrolment. The secondary endpoints are changes in coronary total plaque volume (mm3), plaque burden (%), plaque composition (mm3, %), high-risk plaque characteristics detected using CCTA and CACS determined using CT.Ethics and dissemination Ethics committee approval for this study was obtained from the review boards of Fuwai Hospital (No.2022-1787) and all other study sites. Written informed consent will be obtained from all participants. The results of this study will be published in peer-reviewed journals and reported at international conferences.Trial registration number NCT05462262.